1999
DOI: 10.1525/ac.1999.10.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Ritual Body Postures, Channeling, and the Ecstatic Body Trance

Abstract: In this discussion, attention is focused on the neurophysiological changes recorded in the laboratory during experiences termed religious, since they facilitate contact with the alternate, the sacred reality. The experiences examined are "ritual body posture and ecstatic trance" and "channeling," that is possession. Contrary to previously held opinion based solely on observation, laboratory tests reveal certain differences, indicating that we are dealing with two distinct, albeit closely related, ASC's. Keywor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Earlier EEG studies [9] , [10] were criticized because of the uncontrolled movements of the participants [16] , [17] . However, Guttmann et al [18] observed specific brain wave patterns, characterized by low frequency theta waves, in experienced participants using body postures described by Goodman [4] , [19] and being exposed to rhythmic rattle sequences. More importantly, shamanistic practices have been reported to induce beneficial therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier EEG studies [9] , [10] were criticized because of the uncontrolled movements of the participants [16] , [17] . However, Guttmann et al [18] observed specific brain wave patterns, characterized by low frequency theta waves, in experienced participants using body postures described by Goodman [4] , [19] and being exposed to rhythmic rattle sequences. More importantly, shamanistic practices have been reported to induce beneficial therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…The following RBPs were practiced: (a) Bear Posture, (b) Olmecic Prince, (c) Saami Shaman, and (d) South Moravian Woman (Figure 2). The healing RBPs include the Bear Posture and the South Moravian Woman (Goodman & Nauwald, 2003). They are related to personal aims, aims including others, the environment (e.g., animals), or archetypes (e.g., mother Earth) (Gore, 1995).…”
Section: Design Materials and Methodsmentioning
confidence: 99%
“…They are related to personal aims, aims including others, the environment (e.g., animals), or archetypes (e.g., mother Earth) (Gore, 1995). The overall goal is the restoration of the body-psycho-social-spiritual balance (Goodman & Nauwald, 2003; Gore, 1995). The Bear Posture has its origin in a wooden carving made by Native Americans on the northwest coast of present-day Canada some 7,000 years ago (Goodman, 1999).…”
Section: Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kalahari !Kung dance for hours while frequently assuming ritualized postures (Goodman, 2003). The Sami people of Lapland use monotonous chanting (joiking), aborigines of Australia play the didgeridoo, and the Bön Po shamans of Central Asia ring bells, all with the same non-ordinary sensory condition in mind (Ingerman and Wesselman, 2010).…”
mentioning
confidence: 99%